DNA‐Mediated Assembly of Carbon Nanomaterials. Issue 5 (19th May 2022) - Zhu, Xurong; Yan, Xuehui; Yang, Sichang; Wang, Yong; Wang, Shuang; Tian, Ye
Abstract: Carbon nanomaterials (CNMs) have attracted extensive attentions on account of their superior electrical, mechanical, optical, and biological properties. However, the dimensional limit and irregular arrangement have hampered their further application. It is necessary to find an easy, efficient and controllable way to assemble CNMs into well‐ordered array. DNA nanotechnology, owning to the advantages of precise programmability, highly structural predictability and spatial addressability, has been widely applied in the assembly of CNMs. Summarizing the progress and achievements in this field will be of great value to related studies. Herein, based on the different dimensions of CNMs containing 0‐dimensional (0D) carbon dots (CDs), fullerenes, 1‐dimensional (1D) carbon nanotubes (CNTs) and 2‐dimensional (2D) graphene, we introduced the conjugation strategies between DNA and CNMs, their different assembly methods and their applications. In addition, we also discuss the existing challenges and future opportunities in the field. Abstract : The dimensional limit and irregular arrangement have hampered the potential applications of carbon nanomaterials (CNMs). Therefore, it is essential to find an efficient and controllable way to assemble CNMs into well‐ordered arrays. This Review summarizes progress in the field of DNA nanotechnology regarding the assembly of CNMs, and discusses their precise programmability, high structural predictability, and spatial addressability.